The different paths of feminism in Portugal (from the end of 19th to the present) - Baptista, V.; Marques Alves, P. (VIII Conference of the Italian Association of Women Historians – Gender History: Paths, Intersections, Perspectives, 2021)
Panel - The aim of this panel is to reflect on the paths of feminism in Portugal, Italy, and Brazil in an alternative perspective to the one which is currently dominant. If we look at feminisms on a universal level, can we talk about the "three waves" of feminism as commonly used? What realities and representations are there in the feminisms in the countries of southern Europe mentioned and in Brazil, in a period from the 19th century to the present day? Working women, and declared feminists, have confronted male power acting differently. We will pay attention to the stereotypes that have characterized the binomial woman/worker. Finally, we intend to reflect on the contribution of feminism in the formation of teachers who act as teachers in Higher Education. It is through this research on teacher training that we can link the beginning of feminism in Brazil to the abolitionism that put an end to slavery at the end of the 19th century. The transnational path of feminism that we have undertaken shows that it has not been in harmony in the two countries of Southern Europe and in Brazil, a country that has also been a target of European colonisation for centuries, with the result that indigenous women have been doubly subjugated. Paper - The paths of feminism have varied internationally. Hence, we will reflect on the vision of the three waves of feminism. Working women, and declared feminists, have confronted male power acting differently. The place of speech of the women's movements has been progressive to the present. We have privileged iconographic sources and various texts of the epochs.